Development and quality evaluation of probiotic shrikhand - K. Reshma Ramakrishnan; K. Radha; C.T. Sathian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Probiotic shrikhand was prepared by incorporating probiotic Bacillus coagulans culture along with curd starter culture. The probiotic and control shrikhand samples were examined for the physico-chemical, microbiological and sensory properties. There was no significant difference in fat, ash and protein content between control and probiotic shrikhand. Sensory quality of the probiotic shrikhand was similar to that of control. There existed a significant difference in acidity and total solids content between control and probiotic shrikhand. Probiotic count could be maintained within the minimum recommended level during 15 days of refrigerated storage.